2015
DOI: 10.1038/ki.2014.351
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Na/HCO3 cotransporter sensitivity to insulin may promote hypertension in metabolic syndrome

Abstract: Hyperinsulinemia can contribute to hypertension through effects on sodium transport. To test whether the stimulatory effect of insulin on renal proximal tubule sodium transport is preserved in insulin resistance, we compared the effects of insulin on abdominal adipocytes and proximal tubules in rats and humans. Insulin markedly stimulated the sodium-bicarbonate cotransporter (NBCe1) activity in isolated proximal tubules through the phosphoinositide 3-kinase (PI3-K) pathway. Gene silencing in rats showed that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 48 publications
5
73
0
1
Order By: Relevance
“…These phenotypes are not seen in PT-specific IRS1 or IRS2 single-knockout mice, suggesting that each of the IRSs can compensate for the lack of the other in the PTs. This redundancy is not seen in insulin-mediated sodium reabsorption in the PTs, in which IRS2 plays a pivotal role (35,36), or in the regulation of glucose and lipid metabolism in the liver, in which IRS1 and IRS2 show functional differences (16), although FoxO1 is shared as the key downstream molecule of insulin signaling.…”
Section: Discussionmentioning
confidence: 96%
“…These phenotypes are not seen in PT-specific IRS1 or IRS2 single-knockout mice, suggesting that each of the IRSs can compensate for the lack of the other in the PTs. This redundancy is not seen in insulin-mediated sodium reabsorption in the PTs, in which IRS2 plays a pivotal role (35,36), or in the regulation of glucose and lipid metabolism in the liver, in which IRS1 and IRS2 show functional differences (16), although FoxO1 is shared as the key downstream molecule of insulin signaling.…”
Section: Discussionmentioning
confidence: 96%
“…Adipokines released from adipose tissue in obesity are related to increased sympathetic nerve activity, 37 and insulin resistance (reflected by homeostasis model assessment-insulin resistance index) may also promote hypertension. 38 These factors working in concert might increase MAP in Obese-HT compared to Lean-HT. Due to increased pressure load, cardiac oxygen demand (rate-pressure-product) rises.…”
Section: Discussionmentioning
confidence: 98%
“…We also observed that IR markers were more pronounced in SAH than in normal blood pressure in all groups, that is, women with c-PCOS, ov-PCOS, and controls. Indeed, IR-related compensatory hyperinsulinemia may influence blood pressure through an autonomic nervous system imbalance (30,31), increased renal sodium reabsorption, and decreased nitric oxide production (32)(33)(34) in distinct populations. Regarding PCOS phenotypes, we have previously shown that patients with c-PCOS present subclinical autonomic dysfunction in comparison with controls, and that women with ov-PCOS present intermediate heart rate variability indexes in relation to c-PCOS and control groups (10).…”
Section: Figurementioning
confidence: 99%